نظرية الأرباح في الشريعة والقانون - منصور، عيسى ضيف الله (Kulliyat Ahmad Ibrahim li al-Qanun, al-Jami'ah al-Islamiyah al-'Alamiyah bi- Maliziya, 2005)
"The theory of profit" is considered as an Islamic and legal theory that aims at explaining the very character of profit from a theoretical perspective. The thesis advocates that the profit is the result of work, capital, risk, expenses and the income exceeding the capital. These are the elements of profit that have been adopted by this theory. The research has applied "the theory of profit" to modem companies and financing contracts to determine whether they are profitable or not through investigating the nature of the income generated by them. The researcher has followed an inductive methodology in handling the thoughts and rulings pertaining to profit in various academic works and sources. He has also followed an analytical methodology in studying the views of scholars and highlights the importance and the economic indication of profit. In addition, the work has arrived at several Shari’ah and legal conclusions pertaining to profit and its relation to contemporary financial practice. The work has found that profit is a type of capital appreciation and it is an increment that manifests itself in the extra income exceeding the capital after deducting the direct expenses. The study has also established that "according to the theory of profit" the revenue or income resulting from the circulation of the capital in the market through Mudarabah, Murabaha, and Musharakah is a profit in the strict sense and not interest or remuneration or any other kind of revenues. In addition, the study has also revealed the existence of a similarity between Shari’ah and law scholars opinions with respect to the theory of profit pertaining to the rules governing the profit generated by Mudarabah, Murabaha, and Musharakah. As for some other prevailing contracts, the study has shown that they are not profitable such as AlMuzayadah and Al- Ju'alah because they lack one or more of the elements of profit particularly capital and work for profit as these two elements are closely related to the theory of profit. As for legal companies the study has also revealed the existence of some similarity between Shari'ah and law particularly according to the domain in which the capital is invested.